IMAGING OF PHYTOSPHERE COLONIZATION BY GFP (GREEN FLUORESCENT PROTEIN) EXPRESSED EPIPHYTIC PHYLLOSPHERIC BACTERIA - S. Mahmood; M. Ahmed; S. Hasnain (Journal of Animal and Plant Sciences, 2022)
Bacteria living on the aerial parts of plant come from rhizosphere or/and above ground environment. Leaf associated microbes flourish in harsh conditions, adaptable to other environments, have ability to move across plant and colonize the other parts of plants as well. Imaging of GFP-labelled epiphytic phyllospheric bacteria Pseudomonas sp. MehA-P42 on root, stem and leaves of two sunflower hybrids was done by fluorescence microscopy and CLSM (confocal laser scanning microscope). Phyllo-epiphytic bacteria applied to seeds not even reached and colonized the destined aerial parts but also colonized roots and stem surface of plants. The internal localization (in the inter- and intra-cellular compartments of leaves, stems and roots) of GFP-labeled Pseudomonas sp. MehA-P42 was revealed by CLSM. Phyllo-epiphytic bacteria isolated from one sunflower variety (Hysun-39) established an association with another variety (Hysun-33) through colonization in and on the root stem and leaves surface. Study indicated the movement of plant associated bacteria along phytosphere as well as the ability of phyllospheric bacterial isolates to adapt the environment and flourish on the plants other than the native. This supports the field application of the phyllospheric bacterial isolates to seeds, roots of plant or in rhizosphere as plant stimulator and biocontrol agent.
Keywords: GFP; Phyllosphere; colonization; imaging; fluorescent microscopy; CLSM